Exploration of the Implementation of the Deep Learning Approach in the Teaching and Learning Process at SMK Tiwikrama Mamuju: A Qualitative Study - Honjong, Gusnawati (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study aims to explore the implementation of the Deep Learning approach in the teaching and learning process at SMK Tiwikrama Mamuju. The research employed a qualitative design to gain an in-depth understanding of how the approach is applied in classroom practice and how it influences students’ engagement and learning experiences. The population of this study consisted of 30 second-grade students of SMK Tiwikrama Mamuju. Since the total number of students was relatively small, total sampling was applied, resulting in 30 students serving as the research sample. Data were collected through classroom observations, semi-structured interviews with students and teachers, and documentation review of lesson plans and learning materials. The observation focused on instructional strategies, student participation, and learning interactions. Interviews were conducted to obtain detailed insights into students’ perceptions and teachers’ experiences in implementing the Deep Learning approach. Documentation was used to support and validate findings from observations and interviews. The data were analyzed using qualitative descriptive analysis following the interactive model of Huberman and Miles, which includes data reduction, data display, and conclusion drawing/verification. The findings reveal that the implementation of the Deep Learning approach encouraged active student participation, critical thinking, collaborative learning, and deeper conceptual understanding. Students demonstrated increased motivation and engagement during the learning process. However, challenges were identified, including limited instructional time and the need for teacher readiness in designing higher-order learning activities. Overall, the Deep Learning approach contributed positively to improving the quality of the teaching and learning process at SMK Tiwikrama Mamuju.